Development of nanofibrous membrane from recycled polyethene terephthalate bottle by electrospinning - Md Tanvir Hossain; Md Abdus Shahid; Ayub Ali (Elsevier, 2022)
Recycling polyethene terephthalate (PET) bottles has attracted a lot of attention nowadays due to its polluting nature. Researchers are seeking to recycle the substance to minimize its environmental impact. In order to explore their potential use as facemasks, air conditioners, and automobile's air filtration media, this research looks to develop and characterize electrospun nanofibrous membranes made from recycled PET bottle. Scanning electron microscopy (SEM), Fourier-transform infrared radiation (FTIR), universal tensile testing machine, air permeability tester, moisture management tester (MMT), and particle filtration tester were used to examine the morphological structure, bonding behavior, breaking force, air permeability, moisture management, and efficiency of particle filtration of the developed sample respectively. SEM analysis showed a homogeneous and smooth fiber with an average diameter of 198.5 nm and FTIR analysis confirmed a polyethene terephthalate composition. The maximum strength of the nanofibrous membrane was found to be 20 N corresponding to an elongation value of 4.68 mm. The overall moisture management properties (OMCC) appeared as water repellent fabric which would be be washable, and reusable. The average air permeability of the developed sample was obtained 8.59 L/min. In addition, filtration efficiency appeared 97.04% in particle size 0.3 µm. This nanofibrous membrane would be ideal for air filtration due to its high particle filtration performance, adequate mechanical strength, suitable structure, low toxicity, and reusability.